That Other World Personal Experiences of Mystics and Their Mysticism - Cumberland, Stuart C. (Cambridge library collection. Spiritualism and Esoteric Knowledge, 1918)
Although Stuart Cumberland (1857–1922) was renowned for his mind-reading skills, he was a staunch critic of related spiritualist practices. He claimed that many séances and other events that he had seen confirmed his suspicions that 'the chief basis of the movement was money-making'. So he decided to launch his own campaign to uncover the truth about the methods of spirit-mediums, and in this work, published in 1918, he explains many mediums' tricks, such as making tables move using special silk thread, not spiritual aid. He lectured about the subject in places ranging from Cambridge University to Lambeth Palace, and attributed his own success to his ability to read muscle movement, rather than any supernatural communication. Providing a fascinating picture of the changing spiritualist movement, this work illustrates the extent of the social and political influence of some spiritualists, but also how credibility about their practices was being challenged